Palliative care in people with hepatocellular carcinoma: an integrative review (Research, Society and Development, 2020)
Objective: to analyze the palliative care strategies used by health professionals in people with hepatocarcinoma. Method: integrative literature review concerning the topic in the Scielo, Lilacs, PubMed, MEDLINE, and BDENF virtual databases, without language restriction or date of publication. The search was carried out over the months of January and February 2020. Results: the studies indicated a scarcity in scientific productivity in the area, considering that only 12 articles were selected. It was noticed that the palliative care strategies used by health professionals vary, ranging from an individualized treatment to each person up to the management of symptoms with an approach to physical and psychosocial needs, with the valuation of the multi/interprofessional team. Conclusion: this study is expected to encourage other health professionals to develop more publications in order to obtain a vast, updated, and relevant knowledge about strategies in palliative care of people with hepatocellular carcinoma.